Silica formation with nanofiber morphology via helical display of the silaffin R5 peptide on a filamentous bacteriophage. Issue 1 (December 2017) - Song, In-Wong; Park, Hyojung; Park, Jung; Kim, Hyunook; Kim, Seong; Yi, Sung; Jaworski, Justyn; Sang, Byoung-In
Abstract Biological systems often generate unique and useful structures, which can have industrial relevance either as direct components or as an inspiration for biomimetic materials. For fabrication of nanoscale silica structures, we explored the use of the silaffin R5 peptide fromCylindrotheca fusiformis expressed on the surface of the fd bacteriophage. By utilizing the biomineralizing peptide component displayed on the bacteriophage surface, we found that low concentrations (0.09 mg/mL of the R5 bacteriophage, below the concentration range used in other studies) could be used to create silica nanofibers. An additional benefit of this approach is the ability of our R5-displaying phage to form silica materials without the need for supplementary components, such as aminopropyl triethoxysilane, that are typically used in such processes. Because this method for silica formation can occur under mild conditions when implementing our R5 displaying phage system, we may provide a relatively simple, economical, and environmentally friendly process for creating silica nanomaterials.